Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Needle-related pain and distress management during needle-related procedures in children with and without intellectual disability. - Pascolo, Paola; Peri, Francesca; Montico, Marcella; Funaro, Mishelle; Parrino, Roberta; Vanadia, Francesca; Rusalen, Francesca; Vecchiato, Luca; Benini, Franca; Congedi, Sabrina; Barbi, Egidio; Cozzi, Giorgio (Eur J Pediatr, 2018)
Children with intellectual disability frequently undergo needle-related procedures for diagnosis or treatment. Nevertheless, only a few studies deal with pain and distress management during the procedure in this population of children. This study aimed to investigate the number of anxiety and pain management techniques performed during needle procedure in children with intellectual disability (cases) compared to a population of children without intellectual disability (controls). This multicenter cohort study was performed from July 2016 to January 2018 in the pediatric ward of four urban hospitals in Italy. Eligible subjects were children with and without intellectual disability, from 4 to 17 years old, who needed venipuncture or intravenous cannulation for diagnosis or treatment. Use of topical anesthesia, distraction techniques, and physical or verbal comfort during procedures were recorded. Pain and anxiety scores were also recorded. Forty-seven cases and 94 controls were recruited. Three pain- and anxiety-relieving techniques were performed during the procedure in 12 (25%) cases and in 10 controls (11%); two techniques were performed in 23 (50%) cases and in 26 (28%) controls; 12 (25%) cases and 52 (55%) controls received only one.Conclusion: In this series, children with intellectual disability received significantly more relieving techniques, but experienced more pain and anxiety when compared to children without intellectual disability. What is Known: • Children with intellectual disability experience more episodes of pain than cognitively healthy ones, and almost 10% of these episodes are due to medical procedures. What is New: • Children with intellectual disability despite receiving more relieving techniques during a needle-related procedure experienced more pain and anxiety when compared to healthy children.
Keywords: Adolescent; Anxiety; Child; Child, Preschool; Cohort Studies; Female; Humans; Intellectual Disability; Italy; Male; Pain Management; Pain Measurement; Pain, Procedural; Phlebotomy

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Nutrient intakes in an Italian population of infants during the complementary feeding period. - Concina, Federica; Pani, Paola; Bravo, Giulia; Barbone, Fabio; Carletti, Claudia V; Knowles, Alessandra; Ronfani, Luca; Parpinel, Maria (Public Health Nutr, 2018)
OBJECTIVE: To describe the nutrient intakes of an Italian cohort of infants at 6, 9 and 12 months of age. DESIGN: Dietary data were collected using a food diary at three follow-ups (6, 9 and 12 months of age of infants). The infants' dietary data were used to estimate nutrient intakes using the Italian food composition database integrated with data from nutritional labels and the literature. The mean and standard deviation, median and interquartile range, minimum and maximum, and 5th, 25th, 75th and 95th percentiles were calculated for the daily intake of twenty-eight nutrients, with sex differences evaluated using parametric/non-parametric statistical methods. SETTING: A prospective population-based birth cohort.SubjectInfants (n 400) living in the urban area of Trieste (Italy). RESULTS: The sex distribution was fairly balanced at each follow-up. The mean daily intakes of energy and the other twenty-seven nutrients considered were greater in males at all follow-ups. In particular, a significant statistical difference was observed in higher male consumption of cholesterol at 9 months and in energy and carbohydrate intakes at 12 months (P < 0·05). The mean daily intake of proteins was greater than that recommended by the Italian Dietary Reference Values at all follow-ups. CONCLUSIONS: These preliminary results provide a useful basis for understanding the nutrient intake patterns of infants in this area of Italy during the first year of life.

Natalizumab treatment of multiple sclerosis: new insights. - Delbue, Serena; Comar, Manola; Ferrante, Pasquale (Immunotherapy, 2017)
Natalizumab is a monoclonal antibody directed against the α4 chain of the very late activating antigen 4 and α4β7 integrins, present on the leukocytes surface, used as monotherapy for the treatment of relapsing-remitting multiple sclerosis. It substantially reduces relapse rate and the accumulation of disability, but its use is associated with a very adverse event, that is the development of progressive multifocal leukoencephalopathy, a fatal demyelinating disease of the CNS, due to the lytic replication of the human polyomavirus JC. The main focus of the review is to describe the newest insights on natalizumab, its current use in the clinical practice, the natalizumab-treated patients' management and the risk stratification related to the progressive multifocal leukoencephalopathy development.
Keywords: Animals; Drug-Related Side Effects and Adverse Reactions; Humans; Immunotherapy; Integrin alpha Chains; Integrin alpha4; Integrin beta Chains; JC Virus; Leukoencephalopathy, Progressive Multifocal; Multiple Sclerosis, Relapsing-Remitting; Natalizumab; Risk; Virus Activation; Virus Replication

Neuroimaging Changes in Menkes Disease, Part 1. - Manara, R; D'Agata, L; Rocco, M C; Cusmai, R; Freri, E; Pinelli, L; Darra, F; Procopio, E; Mardari, R; Zanus, C; Di Rosa, G; Soddu, C; et al. (AJNR Am J Neuroradiol, 2017)
Menkes disease is a rare multisystem X-linked disorder of copper metabolism. Despite an early, severe, and progressive neurologic involvement, our knowledge of brain involvement remains unsatisfactory. The first part of this retrospective and review MR imaging study aims to define the frequency rate, timing, imaging features, and evolution of intracranial vascular and white matter changes. According to our analysis, striking but also poorly evolutive vascular abnormalities characterize the very early phases of disease. After the first months, myelination delay becomes evident, often in association with protean focal white matter lesions, some of which reveal an age-specific brain vulnerability. In later phases of the disease, concomitant progressive neurodegeneration might hinder the myelination progression. The currently enriched knowledge of neuroradiologic finding evolution provides valuable clues for early diagnosis, identifies possible MR imaging biomarkers of new treatment efficacy, and improves our comprehension of possible mechanisms of brain injury in Menkes disease.
Keywords: Brain; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Menkes Kinky Hair Syndrome; Neuroimaging; Retrospective Studies; White Matter

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

A Novel Panel of Serum Biomarkers for MPM Diagnosis. - Bonotti, A; Foddis, R; Landi, S; Melaiu, O; De Santi, C; Giusti, L; Donadio, E; Ciregia, F; Mazzoni, M R; Lucacchini, A; Bovenzi, M; Comar, M; et al. (Dis Markers, 2017)
Exposure to asbestos is the main cause of malignant pleural mesothelioma (MPM), a highly aggressive cancer of the pleura. Since the only tools for early detection are based on radiological tests, some authors focused on serum markers (i.e., mesothelin). The aim of this study was the evaluation of new serum biomarkers to be used individually or in combination, in order to improve the outcome of patients whose disease would be diagnosed at an earlier stage. Serum and plasma were available from 43 subjects previously exposed to asbestos and 27 MPM patients, all being epithelioid type. All the new markers found differentially expressed in MPM and healthy subjects, by proteomic and genomic approaches, have been validated in the serum by the use of specific ELISA. The combined approach, using tools of genomics and proteomics, is found to be highly innovative for this type of disease and led to the identification of new serum markers in the diagnosis of MPM. These results, if confirmed in a larger series, may have a strong impact in this area, because early detection of this cancer in people at high risk could significantly improve the course of the disease and the clinical approach to an individualized therapy.
Keywords: Aged; Biomarkers, Tumor; Blood Proteins; Case-Control Studies; Female; Humans; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Proteome

Nationwide study of headache pain in Italy shows that pain assessment is still inadequate in paediatric emergency care. - Benini, Franca; Piga, Simone; Zangardi, Tiziana; Messi, Gianni; Tomasello, Caterina; Pirozzi, Nicola; Cuttini, Marina (Acta Paediatr, 2016)
AIM: Italian national guidelines on pain management were published in 2010, but there is little information on how effective pain management is in paediatric emergency care, with other countries reporting poor levels. Using headache as an indicator, we described pain assessment in Italian emergency departments and identified predictors of algometric scale use. METHODS: All Italian paediatric and maternal and child hospitals participated, plus four general hospitals. Data on all children aged 4-14 years admitted during a one-month period with headache as their chief complaint were abstracted from clinical records. Multivariable analyses identified predictors of algometric assessment, taking into account the cluster study design. RESULTS: We studied 470 admissions. During triage, pain was assessed using a standardised scale (41.5%), informally (15.5%) or was not recorded (42.9%). Only 32.1% of the children received analgesia in the emergency department. The odds ratios for predictors of algometric assessment were non-Italian nationality (3.6), prehospital medication (1.8), admission to a research hospital (7.3) and a more favourable nurses-to-admissions ratio of 10.8 for the highest versus lowest tertile. CONCLUSION: Despite national guidelines, paediatric pain assessment in Italian emergency care was suboptimal. Hospital variables appeared to be stronger predictors of adequate assessment than patient characteristics.

Non-additive genome-wide association scan reveals a new gene associated with habitual coffee consumption. - Pirastu, Nicola; Kooyman, Maarten; Robino, Antonietta; van der Spek, Ashley; Navarini, Luciano; Amin, Najaf; Karssen, Lennart C; van Duijn, Cornelia M; Gasparini, Paolo (Sci Rep, 2016)
Coffee is one of the most consumed beverages world-wide and one of the primary sources of caffeine intake. Given its important health and economic impact, the underlying genetics of its consumption has been widely studied. Despite these efforts, much has still to be uncovered. In particular, the use of non-additive genetic models may uncover new information about the genetic variants driving coffee consumption. We have conducted a genome-wide association study in two Italian populations using additive, recessive and dominant models for analysis. This has uncovered a significant association in the PDSS2 gene under the recessive model that has been replicated in an independent cohort from the Netherlands (ERF). The identified gene has been shown to negatively regulate the expression of the caffeine metabolism genes and can thus be linked to coffee consumption. Further bioinformatics analysis of eQTL and histone marks from Roadmap data has evidenced a possible role of the identified SNPs in regulating PDSS2 gene expression through enhancers present in its intron. Our results highlight a novel gene which regulates coffee consumption by regulating the expression of the genes linked to caffeine metabolism. Further studies will be needed to clarify the biological mechanism which links PDSS2 and coffee consumption.

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

New lenses to look at preeclampsia. - Zullino, Sara; Di Martino, Daniela; Stampalija, Tamara; Ferrazzi, Enrico (Gynecol Endocrinol, 2015)

Next-generation sequencing and its initial applications for molecular diagnosis of systemic auto-inflammatory diseases. - Rusmini, Marta; Federici, Silvia; Caroli, Francesco; Grossi, Alice; Baldi, Maurizia; Obici, Laura; Insalaco, Antonella; Tommasini, Alberto; Caorsi, Roberta; Gallo, Eleonora; Olivieri, Alma Nunzia; Marzano, AngeloValerio; et al. (Ann Rheum Dis, 2015)
OBJECTIVES: Systemic auto-inflammatory disorders (SAIDs) are a heterogeneous group of monogenic diseases sharing a primary dysfunction of the innate immune system. More than 50% of patients with SAID does not show any mutation at gene(s) tested because of lack of precise clinical classification criteria and/or incomplete gene screening. To improve the molecular diagnosis and genotype interpretation of SAIDs, we undertook the development of a next-generation sequencing (NGS)-based protocol designed to simultaneous screening of 10 genes. METHODS: Fifty patients with SAID, already genotyped for the respective causative gene(s), were massively sequenced for the coding portions of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12, NOD2, PSTPIP1, IL1RN, LPIN2 and PSMB8. Three different bioinformatic pipelines (Ion Reporter, CLC Bio Genomics Workbench, GATK-based in-house workflow) were compared. RESULTS: Once resulting variants were compared with the expected mutation list, no workflow turned out to be able to detect all the 79 variants known in the 50 DNAs. Additional variants were also detected, validated by Sanger sequencing and compared to assess true and false positive detection rates of the three workflows. Finally, the overall clinical picture of 34 patients was re-evaluated in the light of the new mutations found. CONCLUSIONS: The present gene panel has resulted suitable for molecular diagnosis of SAIDs. Moreover, genotype-phenotype correlation has confirmed that the interpretation of NGS data in patients with an undefined inflammatory phenotype is remarkably difficult, thus supporting the need of evidence-based and validated clinical criteria to be used concurrently with the genetic analysis for the final diagnosis and classification of patients with SAIDs.

NLRP1 and NLRP3 polymorphisms in mesothelioma patients and asbestos exposed individuals a population-based autopsy study from North East Italy. - Borelli, Violetta; Moura, Ronal R; Trevisan, Elisa; Crovella, Sergio (Infect Agent Cancer, 2015)
NRLP1 (rs12150220, rs9889625, rs9900356, rs6502867, rs2670660) and NLRP3 (rs35829419, rs10754558) polymorphisms have been analyzed in 69 subjects with documented asbestos exposure and death for malignant pleural mesothelioma and 59 patients with documented asbestos exposure but death for other causes, all from a North East Italy. No association was found between NLRP1 and NLRP3 polymorphisms and susceptibility to develop mesothelioma using the general, dominant or recessive models. Also haplotype analysis did not reveal any significant association with mesothelioma. Our findings, being controversial with respect to another study on Italian patients, do suggest the need of further studies to unravel the contribution of NLRP1 and NLRP3 in susceptibility to mesothelioma.

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

The novel dual PI3K/mTOR inhibitor NVP-BGT226 displays cytotoxic activity in both normoxic and hypoxic hepatocarcinoma cells. - Simioni, Carolina; Cani, Alice; Martelli, Alberto M; Zauli, Giorgio; Alameen, Ayman A M; Ultimo, Simona; Tabellini, Giovanna; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is one of the most common lethal human malignancies worldwide and its advanced status is frequently resistant to conventional chemotherapeutic agents and radiation. We evaluated the cytotoxic effect of the orally bioavailable dual PI3K/mTOR inhibitor, NVP-BGT226, on a panel of HCC cell lines, since hyperactivated PI3K/Akt/mTOR signaling pathway could represent a biomolecular target for Small Inhibitor Molecules in this neoplasia. We analyzed the drug activity in both normoxia and hypoxia conditions, the latter playing often a relevant role in the induction of chemoresistance and angiogenesis.In normoxia NVP-BGT226 caused cell cycle arrest in the G0/G1 phase of the cell cycle, induced apoptosis and autophagy at low concentrations. Interestingly the drug inactivated p-Akt and p-S6 at < 10 nM concentration.In hypoxia NVP-BGT226 maintained its cytotoxic efficacy at the same concentration as documented by MTT assays and Western blot analysis. Moreover, the drug showed in hypoxia inhibitory properties against angiogenesis by lowering the expression of the transcription factor HIF-1α and of VEGF.Our results indicate that NVP-BGT226 has a potent cytotoxic effect on HCC cell lines also in hypoxia condition, thus emerging as a potential candidate for cancer treatment in HCC targeted therapy.

A neonate with a 'milky' blood. What can it be? - Bordugo, Andrea; Carlin, Eva; Demarini, Sergio; Faletra, Flavio; Colonna, Franco (Arch Dis Child Fetal Neonatal Ed, 2014)
Keywords: Female; Humans; Hyperlipoproteinemia Type IV; Infant, Newborn; Lipoprotein Lipase; Milk Proteins; Mutation

Neutralizing and IgG antibodies against simian virus 40 in healthy pregnant women in Italy. - Comar, Manola; Wong, Connie; Tognon, Mauro; Butel, Janet S (PLoS One, 2014)
OBJECTIVE: Polyomavirus simian virus 40 (SV40) sequences have been detected in various human specimens and SV40 antibodies have been found in human sera from both healthy individuals and cancer patients. This study analyzed serum samples from healthy pregnant women as well as cord blood samples to determine the prevalence of SV40 antibodies in pregnancy. METHODS: Serum samples were collected at the time of delivery from two groups of pregnant women as well as cord bloods from one group. The women were born between 1967 and 1993. Samples were assayed by two different serological methods, one group by neutralization of viral infectivity and the other by indirect ELISA employing specific SV40 mimotopes as antigens. Viral DNA assays by real-time polymerase chain reaction were carried out on blood samples. RESULTS: Neutralization and ELISA tests indicated that the pregnant women were SV40 antibody-positive with overall prevalences of 10.6% (13/123) and 12.7% (14/110), respectively. SV40 neutralizing antibodies were detected in a low number of cord blood samples. Antibody titers were generally low. No viral DNA was detected in either maternal or cord bloods. CONCLUSIONS: SV40-specific serum antibodies were detected in pregnant women at the time of delivery and in cord bloods. There was no evidence of transplacental transmission of SV40. These data indicate that SV40 is circulating at a low prevalence in the northern Italian population long after the use of contaminated vaccines.

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

NF-κB pathways in hematological malignancies. - Gasparini, Chiara; Celeghini, Claudio; Monasta, Lorenzo; Zauli, Giorgio (Cell Mol Life Sci, 2014)
The nuclear factor κB or NF-κB transcription factor family plays a key role in several cellular functions, i.e. inflammation, apoptosis, cell survival, proliferation, angiogenesis, and innate and acquired immunity. The constitutive activation of NF-κB is typical of most malignancies and plays a major role in tumorigenesis. In this review, we describe NF-κB and its two pathways: the canonical pathway (RelA/p50) and the non-canonical pathway (RelB/p50 or RelB/p52). We then consider the role of the NF-κB subunits in the development and functional activity of B cells, T cells, macrophages and dendritic cells, which are the targets of hematological malignancies. The relevance of the two pathways is described in normal B and T cells and in hematological malignancies, acute and chronic leukemias (ALL, AML, CLL, CML), B lymphomas (DLBCLs, Hodgkin's lymphoma), T lymphomas (ATLL, ALCL) and multiple myeloma. We describe the interaction of NF-κB with the apoptotic pathways induced by TRAIL and the transcription factor p53. Finally, we discuss therapeutic anti-tumoral approaches as mono-therapies or combination therapies aimed to block NF-κB activity and to induce apoptosis (PARAs and Nutlin-3).
Keywords: Antineoplastic Agents; B-Lymphocytes; Carcinogenesis; Dendritic Cells; Gene Expression Regulation, Neoplastic; Hematologic Neoplasms; Humans; Imidazoles; Macrophages; NF-kappa B; Piperazines; Signal Transduction; T-Lymphocytes; TNF-Related Apoptosis-Inducing Ligand; Transcription Factor RelA; Transcription Factor RelB; Tumor Suppressor Protein p53

NLRP3 polymorphism is associated with protection against human T-lymphotropic virus 1 infection. - Kamada, Anselmo Jiro; Pontillo, Alessandra; Guimarães, Rafael Lima; Loureiro, Paula; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Mem Inst Oswaldo Cruz, 2014)
Inter-individual heterogeneity in the response to human T-lymphotropic virus 1 (HTLV-1) infection has been partially attributed to host genetic background. The antiviral activity of the inflammasome cytoplasmic complex recognises viral molecular patterns and regulates immune responses via the activation of interleukin (IL)-1 family (IL-1, IL-18 and IL-33) members. The association between polymorphisms in the inflammasome receptors NLRP1 and NLRP3 and HTLV-1 infection was evaluated in a northeastern Brazilian population (84 HTLV-1 carriers and 155 healthy controls). NLRP3 rs10754558 G/G was associated with protection against HTLV-1 infection (p = 0.012; odds ratio = 0.37). rs10754558 affects NLRP3 mRNA stability; therefore, our results suggest that higher NLRP3 expression may augment first-line defences, leading to the effective protection against HTLV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Female; Genetic Predisposition to Disease; HTLV-I Infections; Human T-lymphotropic virus 1; Humans; Inflammasomes; Interleukin-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective Factors

No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult

Non-classical MHC-I human leukocyte antigen (HLA-G) in hepatotropic viral infections and in hepatocellular carcinoma. - Catamo, Eulalia; Zupin, Luisa; Crovella, Sergio; Celsi, Fulvio; Segat, Ludovica (Hum Immunol, 2014)
The human leukocyte antigen (HLA)-G is a "nonclassical" major histocompatibility complex (MHC) class Ib gene, located at chromosome 6, in the 6p21.3 region. The HLA-G presents immunomodulatory functions essential in pregnancy for the tolerance of the semi-allogenic fetus, but an abnormal expression of HLA-G has been observed in numerous pathological conditions, such as tumors, autoimmune diseases and viral infections. In recent years, numerous studies have assessed the clinical relevance of HLA-G expression in different types of cancer: in general, a higher HLA-G expression correlates with a lower survival rate or a shorter disease-free survival. Altered expression of HLA-G has been found in both HCV and HBV infection, and some genetic polymorphisms have been associated with altered susceptibility/disease development for these infections, however, whether the biologic role of HLA-G in HCV and HBV infection is beneficial or hazardous, it is not completely clear. In the context of hepatocellular carcinoma, HLA-G has shown a potential diagnostic role, moreover a prognostic value in HCC patients has been also attributed to HLA-G molecules. We revise here the role of HLA-G in hepatotropic HBV/HCV infections and in hepatocellular carcinoma (HCC).
Keywords: Carcinoma, Hepatocellular; Female; Genetic Predisposition to Disease; Hepatitis B; Hepatitis C; HLA-G Antigens; Humans; Immune Tolerance; Liver Neoplasms; Polymorphism, Genetic; Pregnancy

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

A novel deletion mutation involving TMEM38B in a patient with autosomal recessive osteogenesis imperfecta. - Rubinato, Elisa; Morgan, Anna; D'Eustacchio, Angela; Pecile, Vanna; Gortani, Giulia; Gasparini, Paolo; Faletra, Flavio (Gene, 2014)
Osteogenesis imperfecta (OI) is a hereditary bone disease characterized by decreased bone density and multiple fractures, usually inherited in an autosomal dominant manner. Several gene encoding proteins related to collagen metabolism have been described in some cases of autosomal recessive OI (including CRTAP, LEPRE1, PPIB, FKBP65, SERPINF1, BMP1, WNT1, FKBP10). Recently, TMEM38B, a gene that encodes TRIC-B, a monovalent cation-specific channel involved in calcium flux from intracellular stores and in cell differentiation, has been associated with autosomal recessive OI. Here, we describe the second deletion-mutation involving the TMEM38B gene in an 11 year-old Albanian female with a clinical phenotype of OI, born to parents with suspected consanguinity. SNP array analysis revealed a homozygous region larger than 2 Mb that overlapped with the TMEM38B locus and was characterized by a 35 kb homozygous deletion involving exons 1 and 2 of TMEM38B gene.
Keywords: Child; Chromosomes, Human, Pair 19; DNA Mutational Analysis; Exons; Female; Genes, Recessive; Homozygote; Humans; Ion Channels; Osteogenesis Imperfecta; Sequence Deletion

Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid

A novel P2RX2 mutation in an Italian family affected by autosomal dominant nonsyndromic hearing loss. - Faletra, Flavio; Girotto, Giorgia; d'Adamo, Adamo Pio; Vozzi, Diego; Morgan, Anna; Gasparini, Paolo (Gene, 2014)
Hereditary hearing loss (HHL) is a common disorder accounting for at least 60% of prelingual deafness. It is characterized by a large genetic heterogeneity, and despite the presence of a major gene, still there is a need to search for new causative mutations/genes. Very recently, a mutation within ATP-gated P2X(2) receptor (ligand-gated ion channel, purinergic receptor 2) gene (P2RX2) at DNFA41 locus has been reported leading to a bilateral and symmetrical sensorineural non-syndromic autosomal dominant HHL in two Chinese families. We performed a linkage analysis in a large Italian family with a dominant pattern of inheritance showing a significant 3.31 LOD score in a 2Mb region overlapping with the DNFA41 locus. Molecular analyses of P2RX2 identified a novel missense mutation (p.Gly353Arg) affecting a residue highly conserved across species. Visual inspection of the protein structure as obtained from comparative modeling suggests that substitution of the small glycine residue with a charged bulky residue such as an arginine that is close to the 'neck' of the region responsible for ion channel gating should have a high energetic cost and should lead to a severely destabilization of the fold. The identification of a second most likely causative mutation in P2RX2 gene further supports the possible role of this gene in causing autosomal dominant HHL.
Keywords: Amino Acid Sequence; Deafness; European Continental Ancestry Group; Female; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Receptors, Purinergic P2X2

The non-genotoxic activator of the p53 pathway Nutlin-3 shifts the balance between E2F7 and E2F1 transcription factors in leukemic cells. - di Iasio, Maria Grazia; Zauli, Giorgio (Invest New Drugs, 2013)
The effect of Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, was investigated on the steady-state mRNA levels of the transcription factors E2F1 and E2F7 in a cohort of primary B-chronic lymphocytic leukemia (B-CLL) patient samples (n = 15) and normal peripheral blood mononuclear cells (PBMC). A 24-h treatment with Nutlin-3 significantly down-regulated E2F1 and promoted the concomitant up-regulation of E2F7 in both leukemic and normal cells. Our data suggest that the ability of Nutlin-3 to up-regulate E2F7 likely represents an important molecular determinant in the anti-proliferative activity of Nutlin-3.
Keywords: Case-Control Studies; Cells, Cultured; E2F1 Transcription Factor; E2F7 Transcription Factor; Gene Expression Regulation, Leukemic; Humans; Imidazoles; In Situ Hybridization, Fluorescence; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; Piperazines; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Tumor Suppressor Protein p53

A novel CRYBB2 missense mutation causing congenital autosomal dominant cataract in an Italian family. - Faletra, Flavio; d'Adamo, Adamo Pio; Pensiero, Stefano; Athanasakis, Emmanouil; Catalano, Dario; Bruno, Irene; Gasparini, Paolo (Ophthalmic Genet, 2013)
Congenital cataract is a leading cause of visual impairment in children and brings approximately 10% of childhood blindness worldwide. Molecular analysis revealed ~60 loci to be associated with several phenotypes of childhood cataracts. Until now, more than 30 loci and 18 genes on different chromosomes have been associated with autosomal dominant congenital cataract (ADCC). Here, we present a three-generation Italian family with a non syndromic ADCC. A linkage analysis carried out using HumanCytoSNP-12 DNA Analysis BeadChip led us to identify ten genomic regions virtually involved in the disease. All the genes located in these regions were scored for possible relationship with ADCC and, according to a strict clinical and genetic selection, 4 genes have been analyzed. A novel sequence variant was found in the CRYBB2 gene (p.Ser143Phe). This variant affects a conserved aminoacid in the third Greek key motif of the protein, cosegregates with the disease phenotype in all affected individuals and is not present both in the unaffected family members and 100 healthy control subjects. Finally, we identified the first CRYBB2 mutation in an Italian family causing a clinical picture of ADCC.
Keywords: Amino Acid Sequence; beta-Crystallin B Chain; Cataract; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genotype; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype

NALP1/NLRP1 genetic variants are associated with Alzheimer disease. - Pontillo, Alessandra; Catamo, Eulalia; Arosio, Beatrice; Mari, Daniela; Crovella, Sergio (Alzheimer Dis Assoc Disord, 2012)
Alzheimer disease (AD) is a complex neurodegenerative disease. Genetic and molecular studies have confirmed that in the human brain, amyloid-β fibrils can induce, through the activation of NALP1 inflammosome, inflammatory and apoptotic responses involved in the pathogenesis of AD. Considering that AD pathogenesis is multifactorial, we hypothesized that NALP1/NLRP1 could be a susceptibility gene involved in the devolvement of the disease. The possible association between 9 selected polymorphisms in the NALP1/NLRP1 gene and AD was evaluated by comparing their frequency distribution in an Italian cohort of AD patients (AD, n = 276) and in a group of Italian sex-matched and age-matched healthy controls without dementia (HC, n = 266). Our study, evidences the association of 4 nonsynonymous polymorphisms in the NLRP1 gene (rs2137722, rs34733791, rs11657747, rs11651595) with AD. The major alleles of all 4 single nucleotide polymorphisms and the corresponding homozygote genotypes were more frequent in AD patients than in healthy controls, suggesting an association of these variants in the predisposition versus the development of the disease. These findings seem to support the previously reported role of NALP1 in neuronal damage, and provide evidence of an association between single nucleotide variations in the NLRP1 gene and AD.
Keywords: Adaptor Proteins, Signal Transducing; Aged, 80 and over; Alzheimer Disease; Apoptosis Regulatory Proteins; Female; Genetic Predisposition to Disease; Genotype; Humans; Italy; Male; Polymerase Chain Reaction; Polymorphism, Single Nucleotide

The negative prognostic value of TRAIL overexpression in oral squamous cell carcinomas does not preclude the potential therapeutic use of recombinant TRAIL. - Carinci, Francesco; Monasta, Lorenzo; Rubini, Corrado; Stramazzotti, Daniela; Palmieri, Annalisa; Melloni, Elisabetta; Knowles, Alex; Ronfani, Luca; Zauli, Giorgio; Secchiero, Paola (Invest New Drugs, 2012)
Keywords: Adult; Aged; Aged, 80 and over; Antineoplastic Agents; Apoptosis; Carcinoma, Squamous Cell; Female; Flow Cytometry; HL-60 Cells; Humans; Immunohistochemistry; Male; Middle Aged; Mouth Neoplasms; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Recombinant Proteins; Risk Assessment; Risk Factors; Survival Analysis; TNF-Related Apoptosis-Inducing Ligand; Tumor Markers, Biological; Up-Regulation; Young Adult

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

NF-κB as a target for modulating inflammatory responses. - Gasparini, Chiara; Feldmann, Marc (Curr Pharm Des, 2012)
The inflammatory response is of major importance in host defence, but is involved in all acute and chronic diseases. Multiple inflammatory cells and molecules are involved. Among the latter, the Nuclear Factor -κB (NF-κB) has been found to be most important and present in all cell types. NF-B regulates the expression of a large number of genes involved in inflammation. NF-κB plays a key role in the orchestration of the multifaceted inflammatory response, not only in the first pro-inflammatory phase, but also later in the regulation of the resolution of inflammation, when anti-inflammatory genes are expressed and apoptosis is induced. The review describes NF-κB and its two pathways: the canonical, mediated by the p65 and p50 subunits, and the non-canonical, mediated by the subunits RelB, p52 and p50. The relevance of the kinases and interactions leading to NF-κB activation is considered in different primary cells (i.e. macrophages, dendritic cells, fibroblasts, cells from inflammatory tissues), together with the response induced and the ligand involved. Then we overview the different steps to NF-B activation that can be targeted (IKKs, IκBα or NF-κB subunits themselves) with various technologies available i.e. small molecules peptides or nucleic acids. A rationale is provided for possible targets to consider, in the light that NF-κB signaling pathways regulates both pro-inflammatory and anti-inflammatory responses. The possibility of using NF-κB targeted dendritic cells in immunotherapy is considered.
Keywords: Acute Disease; Animals; Chronic Disease; Dendritic Cells; Gene Expression Regulation; Humans; Immunotherapy; Inflammation; NF-kappa B; Signal Transduction

NLRP1 polymorphisms in patients with asbestos-associated mesothelioma. - Girardelli, Martina; Maestri, Iva; Rinaldi, Rosa R; Tognon, Mauro; Boldorini, Renzo; Bovenzi, Massimo; Crovella, Sergio; Comar, Manola (Infect Agent Cancer, 2012)
UNLABELLED: BACKGROUND: An increasing incidence of malignant mesothelioma (MM) cases in patients with low levels of asbestos exposure suggests the interference of alternative cofactors. SV40 infection was detected, as co-morbidity factor, only in 22% of asbestos-MM patients from a North-Eastern Italy area. An additional mechanism of injury related to asbestos exposure in MM development has been recently associated to inflammatory responses, principally driven by interleukin (IL)-1 beta (ß) activated within the inflammasome complex.NLRP3 inflammosome has been described as the intracellular sensor for asbestos able to induce inflammasome activation and IL-1ß secretion while NLRP1 is expressed in lung epithelial cells and alveolar macrophages and contributes to the immune response and to survival/apoptosis balance. This study proposes to evaluate the impact of known NLRP3 and NLRP1 polymorphisms in the individual susceptibility to asbestos-induced mesothelioma in subjects from a hyperendemic area for MM. METHODS: 134 Italian patients with diagnosis of mesothelioma due (MMAE, n=69) or not (MMAF, n=65) to asbestos, 256 healthy Italian blood donors and 101 Italian healthy subjects exposed to asbestos (HCAE) were genotyped for NLRP1 (rs2670660 and rs12150220) and NLRP3 (rs35829419 and rs10754558) polymorphisms. RESULTS: While NLRP3 SNPs were not associated to mesothelioma, the NLRP1 rs12150220 allele T was significantly more frequent in MMAE (0.55) than in HCAE (0.41) (p=0.011; OR=1.79) suggesting a predisponent effect of this allele on the development of mesothelioma. This effect was amplified when the NLRP1 rs2670660 allele was combined with the NLRP1 rs12150220 allele (p=0.004; OR=0.52). CONCLUSION: Although NLRP3 SNPs was not involved in mesothelioma predisposition, these data proposed NLRP1 as a novel factor possibly involved in the development of mesothelioma.

Nutlin-3 differentially modulates miRNA34a and miRNA181 versus miR26a and miR155 in p53 proficient and p53 deficient B chronic lymphocytic leukemia (B-CLL) samples. - di Iasio, Maria Grazia; Addobbati, Riccardo; Radillo, Oriano; Voltan, Rebecca (Invest New Drugs, 2012)
Keywords: Down-Regulation; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; MicroRNAs; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

Neuromotor deficits in developmental coordination disorder: evidence from a reach-to-grasp task. - Biancotto, Marina; Skabar, Aldo; Bulgheroni, Maria; Carrozzi, Marco; Zoia, Stefania (Res Dev Disabil, 2011)
Developmental coordination disorder (DCD) has been classified as a specific learning disability, nonetheless the underlying cognitive mechanisms are still a matter of discussion. After a summary of the main hypotheses on the principal neuromotor causes of DCD, this study applies a causal model framework to describe the possible coexistence of more than one deficit in this disorder. For this purpose, kinematic analysis was applied to an ecological task, the reach-to-grasp action, introducing the manipulation of three variables: vision, distance and object size. After a thorough neurological and neuropsychological evaluation, 9 children with DCD (7-9 years old) were selected and compared to 27 age-matched control children. The results suggest that children with DCD have a normal neurological characterization of the reaching and grasping movements, in terms of proximal to distal action, but their grasping aperture (MGA) was always wider with respect to controls, particularly when vision was not allowed. In addition, the performance of children with DCD was always slower, more dependent on vision and more variable than that of controls. The MGA of children with DCD could be explained by a deficit in the internal construction of movement for a forward model, while slowness could be related to a control problem in the neuronal firing of the muscles. The idea of a possible coexistence of these two deficits is discussed in accordance to a causal model framework and also addressed considering recent neurophysiologic evidences.
Keywords: Analysis of Variance; Biomechanical Phenomena; Child; Female; Humans; Male; Motor Skills Disorders; Psychometrics; Psychomotor Performance; Reaction Time; Space Perception

A new case of duplication of the MDS region identified by high-density SNP arrays and a review of the literature. - Faletra, Flavio; Devescovi, Raffaella; Pecile, Vanna; Fabretto, Antonella; Carrozzi, Marco; Gasparini, Paolo (J Appl Genet, 2011)
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Child; Female; Gene Duplication; Humans; Microtubule-Associated Proteins; Myelodysplastic Syndromes; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prognosis

Non-invasive assessment of hemispheric language dominance by optical topography during a brief passive listening test: a pilot study. - Bembich, Stefano; Demarini, Sergio; Clarici, Andrea; Massaccesi, Stefano; Grasso, Domenico Loenardo (Med Sci Monit, 2011)
BACKGROUND: The Wada test is usually used for pre-surgical assessment of language lateralization. Considering its invasiveness and risk of complications, alternative methods have been proposed but they are not always applicable to non-cooperative patients. In this study we explored the possibility of using optical topography (OT)--a multichannel near-infrared system--for non-invasive assessment of hemispheric language dominance during passive listening. MATERIAL/METHODS: Cortical activity was monitored in a sample of healthy, adult Italian native speakers, all right-handed. We assessed changes in oxy-haemoglobin concentration in temporal, parietal and posterior frontal lobes during a passive listening of bi-syllabic words and vowel-consonant-vowel syllables lasting less then 3 minutes. Activated channels were identified by t tests. RESULTS: Left hemisphere showed significant activity only during the passive listening of bi-syllabic words. Specifically, the superior temporal gyrus, the supramarginal gyrus and the posterior inferior parietal lobe were activated. CONCLUSIONS: During passive listening of bi-syllabic words, right handed healthy adults showed a significant activation in areas already known to be involved in speech comprehension. Although more research is needed, OT proved to be a promising alternative to the Wada test for non-invasive assessment of hemispheric language lateralization, even if using a particularly brief trial, which has been designed for future applications with non-cooperative subjects.
Keywords: Acoustic Stimulation; Adult; Cerebrum; Diagnostic Techniques and Procedures; Dominance, Cerebral; Female; Humans; Language; Male; Middle Aged; Oxyhemoglobins; Pilot Projects; Spectroscopy, Near-Infrared

Natural isoprenoids inhibit LPS-induced-production of cytokines and nitric oxide in aminobisphosphonate-treated monocytes. - Marcuzzi, Annalisa; Tommasini, Alberto; Crovella, Sergio; Pontillo, Alessandra (Int Immunopharmacol, 2010)
The inhibition of mevalonate pathway through genetic defects (mevalonate kinase deficiency, MKD) or pharmacologic drugs (aminobisphosphonates) causes a shortage of intermediate compounds and, in particular, of geranylgeranyl-pyrophosphate (GGPP) associated to the activation of caspase-1 and IL-1beta release. Geraniol (GOH), farnesol (FOH), geranylgeraniol (GGOH) and menthol (MOH), due to their isoprenoid structure, are supposed to enter the mevalonate pathway and to by-pass the biochemical block, reconstituting the pathway. Considering the already known side effects of aminobisphosphonates, and the lack of a specific treatment for MKD, we evaluated the impact of these natural isoprenoids compounds in a RAW cell lines chemically treated with the aminobisphosphonate alendronate, and in monocytes isolated from 2 patients affected by MKD. GOH, FOH, GGOH and MOH were all capable to diminish inflammatory marker levels induced by LPS. These natural isoprenoids could be proposed as novel therapeutic approach for the still orphan drug MKD, but also considered for the evaluation of possible inflammatory side effects of aminobisphosphonates.
Keywords: Animals; Cell Line; Cells, Cultured; Child; Child, Preschool; Cytokines; Diphosphonates; Humans; Inflammation; Interleukin-1beta; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Nitric Oxide; Terpenes

Neonatal jaundice and breastfeeding reputation. - Bramuzzo, Matteo; Davanzo, Riccardo (J Hum Lact, 2010)
Keywords: Bottle Feeding; Breast Feeding; Female; Humans; Infant, Newborn; Jaundice, Neonatal; Lactation Disorders; Milk, Human; Risk Factors